Hydroxysteroid Dehydrogenases: An Ongoing Story. Issue 29 (15th April 2020) - Ferrandi, Erica Elisa; Bertuletti, Susanna; Monti, Daniela; Riva, Sergio
Abstract : Hydroxysteroid dehydrogenases (HSDHs) are NAD(P)(H)‐dependent enzymes which belong to the so‐called short‐chain dehydrogenases/reductases (SDR) superfamily. These oxidoreductases catalyze the oxidation/reduction of hydroxyl/keto groups of steroids with high regio‐ and stereoselectivity. HSDHs were the first group of biocatalysts that was investigated by our group, as an original way to support the ongoing research activity in the area of steroid chemistry in the early seventies. Since then, the research activity on these enzymes has followed three main pathways: a) the isolation and production of new HSDHs; b) the development of new efficient enzymatic systems for the in situ regeneration of the cofactor NAD(P)(H); c) the synthetic exploitation of HSDHs. This minireview presents the results that have been published by various research groups in this area in the last 50 years, with a focus on the selective modification of bile acids. Abstract : This minireview provides an overview of the research progress in the discovery and synthetic applications of hydroxysteroid dehydrogenases (HSDHs), enzymes showing an exquisite regio‐ and stereoselectivity, as well as an interesting potential for the development of industrial biocatalyzed processes.